Sosialisasi Serta Praktek Sistem Pendaftaran Tanah - Raditya Feda Rifandhana (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The law is a tool needed by the community, to carry out an activity so that the activity does not violate applicable regulations, regulations are not only regulations in the form of norms, but these regulations can be in the form of matters governing the land registration system. The land registration system is very necessary for someone to register their land in their own/or private name.Purposes of Devotion: The purpose of writing this article is to provide legal understanding and knowledge in terms of the practice of the land registration system, provide legal understanding and knowledge in terms of theory and history of land registration. Method of Devotion: In the Socialization Activities and Practices of the Land Registration System, they are: Submission of Socialization Materials from resource persons to residents who attend the socialization of the land registration system, Questions and Answers from residents to resource persons related to socialization of community service.Results of the Devotion: Land registration on land in Indonesia needs to be carried out an activity where socialization needs to be carried out, so that the community/or residents on Piranha Street Up Alley 13, Tunjungsekar Village, Malang City, can be given their rights in increasing their understanding and knowledge regarding land registration. Furthermore, it can be assisted in terms of understanding legal science, especially related to land law, namely the land registration system in Indonesia.